A chiral cobalt(ii) complex catalyzed enantioselective aza-Piancatelli rearrangement/Diels–Alder cascade reaction. Issue 15 (25th March 2020) - Shen, Bin; He, Qianwen; Dong, Shunxi; Liu, Xiaohua; Feng, Xiaoming
Abstract : An asymmetric aza-Piancatelli rearrangement/Diels–Alder cascade reaction between 2-furylcarbinols and N -(furan-2-ylmethyl)anilines was realized by using a chiral N, N ′-dioxide/cobalt(ii ) complex catalyst. Abstract : A chiral N, N ′-dioxide/cobalt(ii ) complex catalyzed highly diastereoselective and enantioselective tandem aza-Piancatelli rearrangement/intramolecular Diels–Alder reaction has been disclosed. Various valuable hexahydro-2 a, 5-epoxycyclopenta[ cd ]isoindoles bearing six contiguous stereocenters have been obtained in good yields with excellent diastereo- and enantio-selectivities from a wide range of both readily available 2-furylcarbinols and N -(furan-2-ylmethyl)anilines.